2017
DOI: 10.1111/boer.12136
|View full text |Cite
|
Sign up to set email alerts
|

Who Favours the Gay Community? Experimental Evidence Using Charitable Donations

Abstract: In this paper, we conduct an experiment to determine the characteristics of individuals who are more likely to donate to a gay charity. After filling out a questionnaire that includes information on gender, ethnicity, and religiosity, as well as other factors, Israeli undergraduate students are asked to choose two out of four options: participation in a lottery, donation to a gay charity, donation to a religious charity, and donation to an education-focused charity. Our most robust findings are that females an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies also incorporated various dimensions of religiosity such as practice, belief, and experience, as well as the consequence or importance of religion in the participants' lives (Dilmaghani 2018;Diop et al 2018). A few studies also measured religiosity by asking if individuals followed specific religious practices such as keeping Shabbat or Kosher (Sansani and Rozental 2018). Experimental studies often used religious primes such as prayer, religious or God-related thinking, and religious locations (Greenway et al 2018;Morton et al 2020;Thunstrom 2020;Xygalatas et al 2016).…”
Section: Religion and Giving To Out-outgroup And Secular Organizations Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also incorporated various dimensions of religiosity such as practice, belief, and experience, as well as the consequence or importance of religion in the participants' lives (Dilmaghani 2018;Diop et al 2018). A few studies also measured religiosity by asking if individuals followed specific religious practices such as keeping Shabbat or Kosher (Sansani and Rozental 2018). Experimental studies often used religious primes such as prayer, religious or God-related thinking, and religious locations (Greenway et al 2018;Morton et al 2020;Thunstrom 2020;Xygalatas et al 2016).…”
Section: Religion and Giving To Out-outgroup And Secular Organizations Measuresmentioning
confidence: 99%
“…Lyons and Nivison-Smith (2006) show that only a moderate level of attendance increases giving to civic organizations compared to high or low attendance in Australia. Moreover, Mersianova and Schneider (2018) found that in Russia, attendance increases giving to only two secular causes-poverty and victim support causes, whereas Sansani and Rozental (2018) found that religiosity in Israel decreases the probability and amount of giving to gay charities. Shepherd et al (2019) note that not all attendance is equal.…”
Section: Social Network and Service Attendancementioning
confidence: 99%
“…The political leanings of individuals (and therefore the city) may also influence the response to religious and nonreligious requests, as 76 percent of the “secular” Jews identify as center or left politically, while around 48 percent of the “religious” identify as center or left politically (Pew Research Center ). In a different context that examines the relationship across political leanings, gender, and religiosity in Israel, Sansani and Rozental () find that men in Israel and those who lean right politically are more likely to donate money to a religious charity than women and those who lean left politically. This type of positive bias toward the religious may also display itself in the form of less discrimination.…”
Section: Introductionmentioning
confidence: 99%